Elite capture in local fishery management – experiences from post-socialist Albania. (1st January 2012) - Schmidt, Oscar; Theesfeld, Insa
Local governance based on institutions for collective action can help overcome social dilemmas in natural and agricultural resource management. A common path towards local governance is decentralisation, and within this context, a transfer of property rights from central government to local resource users. Yet, despite the successes of many decentralisation policies, the phenomenon of elite capture remains a risk. Our paper investigates elite capture in Albania's Lake Ohrid fishing region. We aim to contribute to the state of knowledge by identifying determinants for elite capture. Our empirical case shows how 'blueprint' approaches, top-down implementation, and weak institutions led to further empowerment of privileged locals, who realise personal gains at the expense of distributional inequity within the community. Specifically original insights are derived from our analysis of implications from the post-socialist context, which we show to facilitate capture due to a common susceptibility for destructive leadership and lacking confidence in collective action.